Space of fresh organic products in supermarket chains: an exploratory analysis - López-Barraza, Lydia María; Olazabal-Lugo, Maricruz (Unidad Editorial UPTC, 2020)
Supermarket chains have been transformed to meet the demands of their customers, through the implementation of marketing strategies such as the organization of the space to reduce shopping times and the diversification of products, expanding the possibility of choice. It is then that the organization of the shelves has become a subject of constant analysis by influencing the products to be offered as their location in the establishment. Therefore, the present study focuses on the physical spaces of the supermarket chains, where elements referring to merchandising, layout and consumer were observed, of fresh organic products (fruis and vegetables) due to their growing purchasing potential. The investigation, through direct observation, explained as the location of the articles analyzed impacts in the motivation for their acquisition. Keywords: merchandising, layout, consumer, supermarket chains, organic products. JELClassification: L11, L22, L81, M21, M31   Received: 06/06/2019.  Accepted: 25/06/2020.  Published: 30/06/2020.